0114 Effects of Sleep Extension and Deprivation on Performance Using a Cognitively Demanding Emotional Task. (27th April 2018) - Alger, S E; Prindle, N; Brager, A J; Doty, T J; Ratcliffe, R H; Ephrem, D; Yarnell, A M; Balkin, T J; Capaldi, V F; Simonelli, G
Abstract: Introduction: Insufficient sleep (chronic restriction or acute sleep deprivation) reduces activity in prefrontal cortex, impairing performance on cognitively demanding tasks. Sleep loss also increases negative-bias, potentially making emotionally negative stimuli especially salient and distracting. The purpose of the present study was to assess the extent to which sleep banking mediates performance on tasks with variable cognitive and emotional demands. Methods: Participants underwent two baseline nights, 7 nights of sleep extension (10hrs/night), 40hrs sleep deprivation, and 1 recovery night (10hrs). Performance on the emotional interference task (EIT) was assessed 3 times: baseline, on the final day of sleep extension, and during sleep deprivation. The EIT involved determining whether lines were parallel or not, with high vs. low cognitive load depending upon the angle of the lines. Results: Performance on high load items significantly improved across sleep extension, regardless of emotional valence (F=9.74, p=.005), while performance on low load items remained consistent. Subsequent sleep deprivation impaired both high and low cognitive load items, with a trend toward greater decline for negative items (F=3.82, p=.06). Those who extended sleep the most relative to their habitual sleep duration showed the greatest improvement during extension (r=.48, p=.02). However, a higher percentage of slow wave sleep (SWS) during latter nights of sleep extension was negatively correlated with performance on high load items (r=-.47, p=.03). This indicates that greater sleep need is linked to greater difficulty with cognitively demanding decision-making. During deprivation, greater performance impairment was associated with longer sleep (r=-.48, p=.02) and higher SWS percentage (r=-.44, p=.04) during recovery sleep, indicating either a) greater susceptibility to sleep deprivation, or b) a greater level of initial sleep debt that was not fully paid off by the prior sleep extension. Conclusion: One week of sleep extension benefits performance on more cognitively demanding decisions likely impaired by greater initial sleep debt. Once sleep is satiated, subsequent sleep deprivation more generally impairs performance and influences on task performance by negative-bias emerge. Support (If Any): Department of Defense Military Operational Medicine Research Program (MOMRP).